Pharmacokinetic profiles, cytotoxicity, and redox metabolism of free and nanoencapsulated curcumin - Copetti P.M. (2022)
© 2022 Elsevier B.V.To analyze the biodistribution, pharmacokinetics, and toxicity of curcumin, we made in silico predictions and performed in vitro tests to demonstrate the differences in the behavior of two cells types (peripheral blood mononuclear cells, PBMCs, and fibroblasts, HFF-1 cell line) treated with curcumin nanocapsule formulations and curcumin solution with respect to cytotoxic effects and redox metabolism. We generated in silico, ADME/Tox profile predictions of curcumin using computational tools. We produced and characterized Eudragit® L-100 and PCL nanocapsules containing curcumin using interfacial deposition of preformed polymer, evaluation of hemolytic potential in erythrocytes, cytotoxic capacity (MTT and dsDNA PicoGreen® assay), and influence on redox metabolism (nitric oxide and DCF production) of PBMCs and HFF-1 treated with curcumin nanoformulations and solution response curves. Computational results showed low biodistribution, no permeation at of the blood-brain barrier (BBB), discreet gastrointestinal absorption, a potential inhibitor of cytochrome P450 isoforms (CYP2C9 and CYP3A4), toxicity class IV, and immunomodulatory action. In vitro tests showed that cell type influenced curcumin behavior. For cytotoxicity, PBMCs showed a concentration-dependent standard, while HFF-1 cells showed that incubation time was an important variable. Redox interactions showed that nanocapsules induced NO production, and all treatments reduced DCF levels. We highlight the pleiotropic biological activities of curcumin and drug release models so that the therapeutic properties of this polyphenol might be better used. Finally, we emphasize that pharmacological safety must always be evaluated in drug delivery systems and, especially, for substances with multiple interaction pathways.